Implication of Behavioral Finance in Investment Decision-making Process - Jahanzeb, Agha; ., Saif-ur-Rehman (Information Management and Business Review, 2012)
Behavioral finance is a structure that supplements some parts of standard finance and replaces other parts. It portrays the behavior of investors and management in decision-making; it illustrates the outcomes of interactions between investors and managers in financial and capital markets. As decisionmaking is an art to undertake complex situations and investors make irrational decisions during their investments. Therefore, it is a unique art to choose a certain alternative from various alternatives available. Although behavioral finance does not claim that every investor would suffer from similar illusion, instead it sheds light on to take necessary initiatives to avoid such illusions, which influence the process of decision-making, particularly while making investments.